Analysis Of The Cognitive Content Of Two Types Of Swimming According To Content Organization Indicators And Their Impact On Technical Performance And Achievement - Al-Hamdani, Muhammad Suhail Najm; Al-Zuhairi, Doaa Subhan Mahmoud (Indonesian Journal of Physical Education and Sport Science, 2024)
Study purpose. University curricula need continuous review, analysis, change, and development due to their strong association with methodological variables. The analysis of the scientific material for swimming (the textbook) according to the indicators of organizing the educational content for swimming activities should be followed to identify the shortcomings and strengths and then follow up on modern educational directives. The study aims to reveal the degree of inclusion of indicators of organizing the educational content for swimming events. Also, it seeks to select and organize proposed educational content for the freestyle and breaststroke swimming events. Material and methods. The researchers used two approaches; the first was the descriptive approach, using content analysis to analyze and evaluate the textbook for the swimming subject (freestyle and breaststroke events). The researchers prepared a list of educational content organization indicators for swimming events. The second approach was the experimental approach, as the design of the control and experimental groups was used, and the number of sample members was (30) female students. The content application took eight weeks, at a rate of one educational unit per week. Results. The results showed that the experimental group students excelled in achievement and technical performance in freestyle and breaststroke swimming due to the proposed educational content selected according to logical and scientific selection criteria. Conclusion. The researchers concluded that proposing and implementing educational programs according to strict scientific and international standards is important. This reflects positively on students' teaching and learning activities.